Development of monopoly mite game as a health promotion media to increase knowledge and understanding about house dust mites in student boarding house - Muhimatul Arifah; Ainur Rofieq; Yuni Pantiwati (Research and Development in Education (RaDEn), 2021)
Student’s knowledge of house dust mite (TDR) is still limited as well as the learning media used are uncomplicated. However, aside from learning outcome, knowledge of environmental health and hygiene are ignored. This study aims to produce health promotion media and analyze the effectiveness. This type of study was conducted by Research and Development (R&D) modified model by Borg & Gall. Data were collected from material expert, media expert, and extensive trial (experiments) that involving 30 students of Biology education department who have taken parasitology courses. As data analysis uses paired t-test (paired sample t-test). The result of the Mite Game Monopoly health media promotion products shows the validation of media experts and material experts are categorized very well with percentages of 97% and 89%. The result of data analysis obtained a value P < 0.05 which means there is a significant difference in the average value of pretest and posttest, it shows an increase of knowledge and understanding of TDR between before and after using the Mite Game Monopoly media.